The Effect of Financial Literature, Income and Herding Bias on Investment Decisions (Study on Students of the Faculty of Economics and Business, Mercu Buana University, Jakarta) - Muhammad Yahya Firdaus; Afifah Ayati; Puji Aprilia (Universitas Mercu Buana, 2022)
This research is a quantitative research which aims to determine the effect of financial literacy, herding bias and income on investment decisions. The population in this study were students of the Faculty of Economics and Business, Mercu Buana University, Jakarta. The sample consisted of 100 respondents. Purposive sampling method. Data collection is done by distributing questionnaires to a predetermined sample via google form. The data analysis technique used the PLS (Partial Least Square) analysis method with Smart PLS3.0 software. The results of this study indicate that: (1) Financial literacy has an influence on investment decisions with a path coefficient value of 0.294; (2) Income has a significant influence on investment decisions with a path coefficient value of 0.412. (3) herding bias does not have a significant effect on investment decisions with a path coefficient value of 0.150.